Empirical Insights into Network Modularity and Brokerage under Remote Work Conditions - Angellia, Filda; Erfina (Indonesian Scientific Publication, 2025)
The COVID 19 pandemic triggered a global shift toward remote work, reshaping how teams coordinate and collaborate. This study investigates the structural consequences of remote work on organizational communication networks using Social Network Analysis (SNA). Drawing on data from Microsoft 365, Slack, and GitHub, the research analyzes metrics such as modularity, E I Index, betweenness centrality, and tie churn to evaluate changes in collaboration structures. We analyzed communication patterns by building weighted interaction networks based on digital activity. These networks were generated from logs of email, chat, and code collaboration tools, structured weekly or monthly depending on platform. These findings underscore the challenges organizations face in maintaining cohesion and innovation in distributed teams. The study highlights async first communication strategies, cross team structures, and digital fluency as critical levers for network resilience. This research contributes empirical benchmarks for evaluating remote collaboration and proposes actionable metrics for organizational design in digital work environments.